Fixed-time consensus of nonlinear multi-agent system with uncertain disturbances based on event-triggered strategy. (July 2022) - Guo, Yanping; Tian, Yun; Ji, Yude; Ge, Zhen
Abstract: This paper presents a fixed-time consensus problem for multi-agent systems (MASs) with nonlinear dynamics and uncertain disturbances, the event-triggered strategy is proposed to address this issue. Firstly, based on event-triggered control theory, a fixed-time consensus protocol is proposed, which can avoid continuous communication and greatly reduces the power consumption of proposed protocols. Secondly, based on graph topology, fixed-time control method and Lyapunov theory, the novel fixed-time consensus criteria of MASs with nonlinearity under Lipschitz condition and uncertain disturbances bounds is derived via the designed protocols. Furthermore, the consensus can be guaranteed by setting the proper parameters, it should be pointed out that for any given initial state, the MASs can reach consensus within the setting time. Thirdly, by utilizing the above control strategy, the MASs have no Zeno behavior. Finally, two simulation examples and the practical application of unmanned air vehicles (UAVs) verify the reliability of proposed control scheme. Highlights: The consensus of MASs with uncertain disturbances based on event-triggered strategy is proposed. The settling time of fixed-time consensus can guarantee under arbitrary initial conditions. The control algorithm can reduce the frequency of control updates and unnecessary communication.